2018
DOI: 10.3389/fevo.2018.00217
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Trait Variability in Andropogon gerardii, a Dominant Grass Species in the US Great Plains

Abstract: The climatic conditions in the North American Great Plains are highly variable, characteristic of an inter-continental climate. Antecedent climate history has impacted the flora of Great Plains grasslands, resulting in high species richness as well as dominance by only a few grass species, such as Andropogon gerardii. While the productivity of A. gerardii is well described, the individual physiological, and morphological characteristics that confer species dominance over wide spatial gradients are not clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Phenotypic plasticity is an important means by which plant species respond and adapt to their environments and novel selective pressures (Matesanz et al., 2010). We found that A. gerardii was plastic across many phenotypes, consistent with other studies (Avolio & Smith, 2013b; Bachle et al., 2018). Intuitively, greater relative growth rates, A net , biomass and root structure were found in wetter treatments (Figure 2), suggesting that greater A net afforded by greater %VWC led to greater biomass and greater root structural complexity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Phenotypic plasticity is an important means by which plant species respond and adapt to their environments and novel selective pressures (Matesanz et al., 2010). We found that A. gerardii was plastic across many phenotypes, consistent with other studies (Avolio & Smith, 2013b; Bachle et al., 2018). Intuitively, greater relative growth rates, A net , biomass and root structure were found in wetter treatments (Figure 2), suggesting that greater A net afforded by greater %VWC led to greater biomass and greater root structural complexity.…”
Section: Discussionsupporting
confidence: 92%
“…Functional variation is known to have a genetic basis among widely distributed A. gerardii ecotypes (Bachle et al., 2018), yet genotypes of this species on a local scale within a single population are evaluated less often (but see Avolio & Smith, 2013b). Due to known inflation of genotypic effects in local‐scale studies (Tack et al., 2012), we suggest more work is needed at the population level to understand how A. gerardii‐ dominated and other native plant communities are shaped by selective pressures.…”
Section: Discussionmentioning
confidence: 99%
“…We used calculated emission ratios to compute emission factors (grams of species X emitted per kilogram of biomass burned) based on the carbon mass balance method [34]. Big bluestem (Andropogon gerardii) is the dominant species in almost 90% of plots at Konza Prairie [35], and remains the dominant grass species over much of the Great Plains [36]. Elemental analysis of dried Andropogon gerardii is 49.1% carbon by weight [37], so there are 491 g of carbon for each kg of dry biomass, which was used along with emission ratios to compute emission factors.…”
Section: Data Reduction and Calculationsmentioning
confidence: 99%
“…Dominant grasses thrive in their native habitats, because each has evolved specialized functional traits as mechanisms of persistence within each region’s disturbance regimes (Anderson 2006 ; Bachle et al 2018 ; Jardine et al 2021 ). These adaptations include but are not limited to: (1) large shallow rooting systems comprised of fine roots that quickly absorb water (Nippert and Knapp 2007 ; Nippert et al 2012 ); (2) belowground meristematic tissues (“bud banks”) which provide new growth after senescence, fire, and grazing (Dalgleish and Hartnett 2006 ; Ott and Hartnett 2015 ; Ott et al 2019 ); and (3) specialized leaf morphology and anatomy to maximize light capture and minimize water loss to decrease the drought effects (Hameed et al 2012 ; Nunes et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research was built around a common garden experimental design, and has yielded many novel insights such as the genotypic changes in local populations (ecotypes) across regions (Mendola et al 2015 ; Maricle et al 2017 ; Galliart et al 2019 ). In addition, other studies have determined that large intraspecific variation in functional traits regulating physiology exists in A. gerardii , enabling a single species to occupy a wide geographic and environmental breadth (Bachle and Nippert 2018 , 2021 ; Bachle et al 2018 ; Westerband et al 2021 ). To date, investigations of genotypic and physiological variability in A. gerardii have provided key perspectives on population-level plasticity across naturally occurring precipitation gradients (Avolio and Smith 2013 ; McAllister et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%